Study of Manure on Growth and Yield of White Glutinous Rice (Oryza Sativa L. Glutinosa) - siti nurjanah; Dewi Ratna Nurhayati; Siswadi Siswadi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2020)
Research on